Race, neighbourhood characteristics and disparities in chemotherapy for colorectal cancer. Issue 3 (3rd December 2009) - Hao, Y; Landrine, H; Jemal, A; Ward, K C; Bayakly, A R; Young, J L; Flanders, W D; Ward, E M
Abstract : Background: Studies have found significant race/ethnic and age differences in receipt of adjuvant chemotherapy for stages III colon and II/III rectal cancers. Little is known about the role of neighbourhood factors in these disparities. Methods: The 4748 Black and White patients from the Georgia Comprehensive Cancer Registry were diagnosed with stages III colon and II/III rectal cancers between 2000 and 2004. Neighbourhood poverty, segregation (% Black residents) and rurality were linked to each patient using census tract identifiers. Multilevel analyses explored the role of neighbourhood characteristics and the nested association of patient race within categories of neighbourhoods in receipt of chemotherapy. Results: Odds of receiving chemotherapy for urban and suburban patients were 38% (95% CI 1.09 to 1.74) and 53% (95% CI 1.20 to 1.94) higher than for rural patients. However, odds of receiving chemotherapy for urban Black patients were 24% (95% CI 0.62 to 0.94) lower than for their White counterparts. Receipt of chemotherapy did not significantly differ between Blacks and Whites residing in suburban or rural areas. Conclusion: Black–White disparities in receipt of chemotherapy among Georgia colorectal cancer patients were confined to urban patients. Disparities in receipt of this treatment for rural patients were found irrespective of patient race. Our findings highlight geographic areas where targeted interventions might be needed.